2016
DOI: 10.1158/1078-0432.ccr-15-3028
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic EWSR1 Fusion Sequence as Highly Sensitive and Dynamic Plasma Tumor Marker in Ewing Sarcoma

Abstract: Genomic fusion sequences represent promising noninvasive biomarkers for improved therapy monitoring in EwS. Until now, response assessment is largely based on MRI and CT imaging, implying restrictions on closely repeated performance and limitations on the differentiation between vital tumor and reactive stromal tissue. Particularly in patients with prognostic unfavorable disseminated disease, ctDNA is a valuable addition for the assessment of therapy response. Clin Cancer Res; 22(17); 4356-65. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 36 publications
1
78
0
1
Order By: Relevance
“…Detection of circulating tumor cells and circulating tumor DNA (“liquid biopsies”) plays an emerging role as non-invasive diagnostic and disease monitoring tool. Liquid biopsies are now being evaluated for neuroblastoma and Ewing sarcoma [8, 9]. …”
Section: Reviewmentioning
confidence: 99%
“…Detection of circulating tumor cells and circulating tumor DNA (“liquid biopsies”) plays an emerging role as non-invasive diagnostic and disease monitoring tool. Liquid biopsies are now being evaluated for neuroblastoma and Ewing sarcoma [8, 9]. …”
Section: Reviewmentioning
confidence: 99%
“…As amplification of the target region is performed with primers binding to separate chromosomal regions and detection of the target amplicon occurs by a probe that is placed on the breakpoint region, these assays offer unprecedented specificity. The feasibility of this approach has also recently been confirmed in Ewing sarcomas . The assays to detect synovial sarcoma t(X;18) ctDNA from cell‐lines showed similar sensitivity and specificity than with myxoid liposarcomas (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…1718 This case highlights the potential utility of circulating tumor DNA as a blood based biomarker for ES, particularly in situations where biopsy confers significant morbidity. Our group has recently demonstrated that EWSR1 fusions can be detected via blood droplet digital PCR in 11/11 ES patients, 7 of which were able to be detected at relapse.…”
Section: Discussionmentioning
confidence: 94%